On vowel duration and intonation of Peruvian Amazonian Spanish - García, Miguel (2014)
In this article, vowel duration in Peruvian Amazonian Spanish is explored through the use of an experimental method. This research takes into account two factors: stress and position in the sentence. Additionally, it offers a formal analysis that unites these findings with the intonational patterns of the Amazonian variety. For comparative purposes, data from Lima Spanish is also examined. The results indicate that, in the Amazonian variety, vowels are phonetically longer than those in the Lima variety. This difference becomes more evident in the stressed vowels and in sentence-final position. Within words, pretonic vowels in the Amazonian variety are shorter than tonic vowels, which themselves are more than twice as long as postonic vowels. In Lima Spanish, on the other hand, vowels within a word measure approximately the same length. Therefore, these results allow us to conclude that, in the Amazonian variety, vowel length contributes to the location of the F0 peak within the temporal boundaries of the stressed syllable, a feature that distinguishes it from other varieties.